Tony, the Hero; Or, A Brave Boy's Adventures with a Tramp - Alger, Horatio, Jr., 1832-1899 (Salt Lake City, UT : Project Gutenberg, 2019)
"Tony, the Hero; Or, A Brave Boy's Adventures with a Tramp" by Horatio Alger, Jr. is a novel written in the late 19th century. The story follows Tony, a 14-year-old boy who leads a vagrant life alongside his uncle, Rudolph, a dark and suspicious tramp. The narrative explores themes of resilience, the desire for a better life, and the quest for identity as Tony grapples with his situation and dreams of a stable future. The opening of the book introduces Tony and Rudolph trudging through a country town in New York. As they converse, it becomes apparent that Tony is weary of the life of a tramp and wishes to break free from it, while Rudolph believes in the independence of their lifestyle. The dynamics of their relationship highlight Tony's internal struggle between loyalty to his guardian and the yearning for a more conventional life. Despite feeling stuck, Tony manages to assert his desire for change, setting the stage for his eventual quest for self-discovery and belonging. (This is an automatically generated summary.)
Tony, the hero -- Whitmarsh's revenge -- The boy in the bush -- The midnight ride -- A thousand a year.
Release date is 2019-07-12
E-text prepared by David Edwards, Martin Pettit, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Short stories; Conduct of life -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; Bildungsromans; Inheritance and succession -- Juvenile fiction; Diligence -- Juvenile fiction; Success -- Juvenile fiction; Tramps -- Juvenile fiction; Runaway teenagers -- Juvenile fiction; Street life -- Juvenile fiction; Criminals -- Juvenile fiction